Understanding issues in mathematical problem solving and modeling: lessons from lesson study - Wake, Geoffrey; Foster, Colin; Swan, Malcolm (2014)
At the heart of our concern, and research, has been to understand how, in classroom learning, students might develop capabilities towards mathematical literacy (Steen, 2001). We have sought to gain insight into how to teach students to be able to apply mathematics effectively to solve problems that arise in a range of different contexts. We have, therefore, researched professional learning communities in which teachers work together and learn from each other, informed by ‘knowledgeable others’ who have research-informed expertise.